Targeting Viral DNA and Promoter Hypermethylation in Salivary Rinses for Recurrent HPV‐Positive Oropharyngeal Cancer. (11th February 2020) - Shen, Sarek; Saito, Yuki; Ren, Shuling; Liu, Chao; Guo, Theresa; Qualliotine, Jesse; Khan, Zubair; Sadat, Sayed; Califano, Joseph A.
Abstract : Objective: The incidence and survivorship of human papillomavirus (HPV)–associated oropharyngeal squamous cell carcinoma (OPSCC) are increasing. Presence of HPV DNA and epigenetic alterations in salivary rinses are independently associated with clinical prognosis. We evaluated the utility of a combined panel in detecting disease recurrence during surveillance. We also assessed the assay's applicability in screening for HPV+ OPSCC. Study Design: Retrospective cohort study. Setting: Two tertiary academic hospitals. Subjects and Methods: Forty‐nine patients with posttreatment OPSCC were enrolled. Separately, 21 treatment‐naive patients and 40 controls were included in the screening analysis. Salivary rinses were obtained from these cohorts and biomarker levels were quantified. Receiver operative characteristic (ROC) curves and multivariate logistic models were used to assess performance of biomarker combinations. Results: Eight patients (16.3%) in the posttreatment cohort developed locoregional recurrence. Recurrence was associated with alcohol use (odds ratio [OR], 6.12; 95% confidence interval [CI], 0.26‐3.79) and advanced nodal disease (OR, 2.21; 95% CI, 1.52‐3.01). A panel of HPV DNA and methylated EDNRB improved detection of recurrent disease (area under the curve [AUC], 0.88) compared to single markers (AUC, 0.69‐0.78). Positive biomarkers preceded clinical detection by 2.4 ± 1.6 months and was associated with nearly 40‐fold risk of recurrence (OR, 36.4; 95% CI, 1.15‐45.22). Within the screening analysis, single biomarkers demonstrated moderate sensitivity and specificity (AUC, 0.59‐0.83) in the detection of primary disease. A panel combining HPV DNA markers with methylated EDNRB and methylated PAX5 improved AUC to 0.93. Conclusion: Detection of high‐risk HPV DNA or aberrant hypermethylation in oral rinses is associated with presence and recurrence of OPSCC. Targeting both markers in saliva may have utility in long‐term surveillance.